WHO Safety Surgical Checklist implementation evaluation in public hospitals in the Brazilian Federal District - Heiko T. Santana; Marise R. de Freitas; Edmundo M. Ferraz; Maria S.N. Evangelista (Elsevier, 2016)
Summary: The World Health Organization (WHO) created the WHO Surgical Safety Checklist to prevent adverse events in operating rooms. The aim of this study was to analyze WHO checklist implementation in three operating rooms of public hospitals in the Brazilian Federal District. A prospective cross-sectional study was performed with pre- (Period I) and post (Period II)-checklist intervention evaluations. A total of 1141 patients and 1052 patients were studied in Periods I and II for a total of 2193 patients. Period I took place from December 2012 to March 2013, and Period II took place from April 2013 to August 2014. Regarding the pre-operatory items, most surgeries were classified as clean-contaminated in both phases, and team attire improved from 19.2% to 71.0% in Period II. Regarding checklist adherence in Period II, "Patient identification" significantly improved in the stage "Before induction of anesthesia". "Allergy verification", "Airway obstruction verification", and "Risk of blood loss assessment" had low adherence in all three hospitals. The items in the stage "Before surgical incision" showed greater than 90.0% adherence with the exception of "Anticipated critical events: Anesthesia team review" (86.7%) and "Essential imaging display" (80.0%). Low adherence was noted in "Instrument counts" and "Equipment problems" in the stage "Before patient leaves operating room". Complications and deaths were low in both periods. Despite the variability in checklist item compliance in the surveyed hospitals, WHO checklist implementation as an intervention tool showed good adherence to the majority of the items on the list. Nevertheless, motivation to use the instrument by the surgical team with the intent of improving surgical patient safety continues to be crucial. Keywords: Surgical checklist, Adverse events, Patient safety, Surgical team, Infection control